A Management and Sustainability Model for Diamond Route (Non-commercial Open Access) Scientific Journals of the Universidad Nacional, Costa Rica: English translation - Mora-Campos, Andrea (2024)
Objective. Describe the construction stages of a structure that organizes good practices derived from the design of a management and sustainability model for Diamond (Non-commercial Open Access) scientific journals of the Universidad Nacional de Costa Rica. Introduction. An assessment of the Latin American, Costa Rican, and institutional contexts was carried out on aspects related to policies on open knowledge during the last 20 years. The institutional route and its chronological record that show the evolution of editorial management of the journals since the creation of the first of these publications, approximately 50 years ago are described. Management model. The development of the scientific journal management model is described considering the conceptualization, guiding principles, work team, support and advisory bodies, financial sustainability, and monitoring and evaluation of the journals. Results. The model’s innovation, adaptability, and alignment with international standards stand out, as well as collaborative work, strategic planning, and institutional protection, all of which led to the creation of tangible products including regulations and a manual of procedures. Conclusions. A capacity for adaptability in the editorial management of scientific journals is crucial for scientific and social progress. This model promotes sustainability and editorial quality with an emphasis on the diamond path, Open Science, and student inclusion, and its international impact has been recognized in promoting science as a public good and resistance to models based on Article Processing Charges (APC). Recommendations. The recommendations are organized with reference to the different sectors that manage scientific communication, highlighting the importance of promoting Non-commercial Open Access, generating venues to discuss the financial sustainability of open knowledge editorial management, and other spaces for international cooperation. Finally, the recognition of scientific communication as a public good must be accompanied by concrete actions that ensure adequate and stable resources that allow maintaining quality editorial management and promote ethical and transparent practices.